Strengthening School-Based Character Education Training for Teachers in Border Schools in Entikong, West Kalimantan - Endang Purwaningsih; Sulistyarini Sulistyarini; Thomy Sastra Atmaja; Shilmy Purnama (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2021)
Entikong is one of the area of West Kalimantan, which is directly adjacent to neighboring Malaysia. Entikong has a significant degradation potential for the younger generation's character values, especially the value of nationalism. One of the efforts that can be made to strengthen nationalism's character is to instill the values of national character in students. However, on the other hand, many teachers do not comprehensively understand the implementation of school-based character education strengthening (PPK) as mandated by the government. Responding to this requires real effort from various parties, including universities, to participate in socializing this excellent program at the school and community levels. The activity was carried out through training to 22 teachers in the Entikong border area to deliver material related to school-based KDP. The implementation of activities is carried out online via zoom meetings. As a result of this activity, teachers can comprehensively know and understand the implementation of school-based KDP for the border area of Entikong, West Kalimantan.